Acoustical simulation of pneumatic mufflers hybridized with metal sintered bronze porous material, a spiral tube, and expansion cones. Issue 3 (September 2022) - Chiu, Min-Chie; Chang, Ying-Chun
This paper aims to eliminate the pneumatic noise using a muffler hybridized with a metal sintered bronzed porous material, a spiral tube, and expansion cones. In this paper three kinds of mufflers (Muffler A: with part AA (a bronze-made sintered porous inlet); Muffler B: with part BB (a casing with a spiral tube and expansion cones); and Muffler C: part AA (a bronze-made sintered porous inlet) + part BB (a casing with a spiral tube and expansion cones)) have been introduced. A finite element method run on the COMSOL software will be adopted in the acoustical analysis of the mufflers. The influence of TL with respect to two kinds of design parameters (QQ: the number of expansion cone; σ1: the acoustical flowing impedance of the acoustical wool) has been assessed. Simulated results reveal that the muffler C with acoustical components of AA and BB is superior to the other two mufflers. Moreover, the design parameters of QQ and σ1 have essential acoustical influence to the muffler C.